Evaluation of blood velocity waveform features in common carotid artery for healthy subjects and cardiovascular patients - Saleh, M.; Azhim, A.; Zulaika, H.; Bagherpour, P.; Kinouchi, Y.; Ibrahim, F. (2014)
Blood flow velocity (BFV) provides the crucial hemodynamics data to diagnose, predict and manage cardiovascular disease including hypertension. The aim of the present study is to investigate the usefulness of envelope waveforms of BFV and its indices in the common carotid artery (CCA) by comparing it between two groups; cardiovascular patient and healthy normal subject. Data are selected to statistically analyze from normal subject (n=202, age range: 20-69) and cardiovascular patient (n=41, mean age: 68.95±10.99). A t-test is used to determine age effect on the normal subject. Multivariate analysis is used to determine the correlation of multiple BFV indices with age. In the healthy subjects, there are negative correlation of resistive index (RI) and vascular elasticity index (VEI), whereas positive correlation of velocity reflection index (VRI) with age (p<0.001). For further analysis, fifty-two healthy subjects were selected from healthy group (age mean: 57.12±4.50) as control after matching their age with cardiovascular patient group. After testing the normality of data, a Student’s t-test is used to determine BFV waveform and its indices in the two groups. In the study, we found that there are significant difference of BFV and indices in cardiovascular patients and normal subjects after controlling the age and gender. In conclusion, the potential of BFV and its indices is confirmed to be used as a reference data for healthcare application and clinical implications.